Early impact of insulin treatment on mortality for hyperglycaemic patients without known diabetes who present with an acute coronary syndrome. Issue 12 (13th May 2007) - Weston, C; Walker, L; Birkhead, J
Abstract : Objective: To determine the effect of insulin for the management of hyperglycaemia in non-diabetic patients presenting with acute coronary syndrome. Methods: An observational study from the MINAP (National Audit of Myocardial Infarction Project) database during 2003–5 in 201 hospitals in England and Wales. Patients were those with a final diagnosis of troponin-positive acute coronary syndrome who were not previously known to have diabetes mellitus and whose blood glucose on admission was ⩾11 mmol/l. The main outcome measure was death at 7 and 30 days. Results: Of 38 864 patients who were not previously known to be diabetic, 3835 (9.9%) had an admission glucose ⩾11 mmol/l. Of patients having a clear treatment strategy, 36% received diabetic treatment (31% with insulin). Mortality at 7 and 30 days was 11.6% and 15.8%, respectively, for those receiving insulin, and 16.5% and 22.1%, respectively, for those who did not. Compared with those who received insulin, after adjustment for age, gender, co-morbidities and admission blood glucose concentration, patients who were not treated with insulin had a relative increased risk of death of 56% at 7 days and 51% at 30 days (HR 1.56, 95% CI 1.22 to 2.0, p<0.001 at 7 days; HR 1.51, 95% CI 1.22 to 1.86, p<0.001 at 30 days). Conclusion: In non-diabetic patients with acute coronary syndrome and hyperglycaemia, treatment with insulin was associated with a reduction in the relative risk of death, evident within 7 days of admission, which persists at 30 days.